Flow cytometric analysis of circulating platelet-monocyte aggregates in whole blood: Methodological considerations - Harding, Scott A.; Din, Jehangir N.; Sarma, Jaydeep; Jessop, Alasdair; Weatherall, Mark; Fox, Keith A.A.; Newby, David E. (Thrombosis and Haemostasis, 2007)
Platelet-monocyte aggregates are increasingly being used to quantify platelet activation.The variables that influence plateletmonocyte aggregates have not been well defined.We sought to determine the effect of blood collection, handling and processing techniques on detected levels of platelet-monocyte aggregates using a flow cytometric assay. Whole blood was labelled with anti-CD14-PE and anti-CD42a-FITC. Thereafter, samples were fixed and red cells lysed.Analysis was performed with the flow cytometer initially triggering on light scatter and then on FL-2 to identify CD14-PE positive monocytes. Platelet-monocyte aggregates were defined as monocytes positive for CD42a. The effect of collection, handling and processing techniques on this assay were assessed. Anticoagulation with heparin (20.1 ± 2.0%), PPACK (16.8 ± 1.9%), sodium citrate (12.3 ± 1.6%) and EDTA (9.5 ± 1.0%) resulted in markedly different levels of pla- gregation was higher in samples obtained from intravenous cannulae compared to those obtained by venepuncture (20.9 ± 3.9% vs.13.8 ± 2.4%,P=0.03).For every 10 minutes of delay prior to processing platelet-monocyte aggregates increased by 2.8% (P=0.0001) in PPACK anticoagulated blood and 1.7% (P=0.01) in citrate anticoagulated blood. Erythrocyte lysis together with fixation does not affect platelet-monocyte aggregation. Plateletmonocyte aggregates remained stable over 24 hours when fixed and stored at 4°C. Multiple handling and processing factors may affect platelet-monocyte aggregation. We recommend the measurement of platelet-monocyte aggregates on samples collected by direct venepuncture, using a direct thrombin inhibitor as the anticoagulant and minimising the time delay before sample fixation.
Keywords: Platelet activation; leukocytes; methods; flow cytometry